2020
DOI: 10.1088/1361-6587/abcab2
|View full text |Cite
|
Sign up to set email alerts
|

On the possibility of limit-cycle-state of peeling mode near stability boundary in the quiescent H-mode

Abstract: A model is proposed for the edge harmonic oscillation, in which the stationary coherent mode is sustained in the almost linear phase as has been observed in JT-60U. We study the coupled dynamics of the peeling mode amplitude and edge pressure gradient. The limit cycle oscillation is predicted. The peeling mode (which is almost in the linear phase) is in a dynamical stationary state with amplitude modulation. In this model, the time scales for the change of parameters that specify magnetic structures (such as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…Together with the fundamental mode of the EHO, the mean temperature gradient was measured to oscillate in a limit cycle with an LCO frequency about a factor 60 lower than the EHO frequency. A limit-cycle model for these oscillations in JT60-U was developed in [51]. With this model it was shown that a limit cycle solution exists near the stability boundary of peeling modes, in which the pressure gradient and peeling mode amplitude oscillate in time, quantitatively consistent with the JT60-U observations.…”
Section: Limit Cycle Oscillationssupporting
confidence: 54%
“…Together with the fundamental mode of the EHO, the mean temperature gradient was measured to oscillate in a limit cycle with an LCO frequency about a factor 60 lower than the EHO frequency. A limit-cycle model for these oscillations in JT60-U was developed in [51]. With this model it was shown that a limit cycle solution exists near the stability boundary of peeling modes, in which the pressure gradient and peeling mode amplitude oscillate in time, quantitatively consistent with the JT60-U observations.…”
Section: Limit Cycle Oscillationssupporting
confidence: 54%